Intelligent instrumentation : principles and applications - Bhuyan, Manabendra (Boca Raton, FL : CRC Press, 2010)
'A reflection of the evolution of topics now covered in instrumentation or sensor engineering courses, this book employs principles-based explanations to delineate the technology. It uses commercial devices or technology to support the theory. The author provides solid answers to the questions: What makes a sensor intelligent? What are the various ways to classify them? How can a classical instrumentation system be provided with the intelligent features? and What are the recent technologies of II/SS? The book includes illustrations, photographs, numerical problems and case studies wherever needed to explain the theory'--
Includes bibliographical references and index.
Keywords: Engineering instruments; Computerized instruments; Detectors; Intelligent control systems; TECHNOLOGY & ENGINEERING / Sensors; TECHNOLOGY & ENGINEERING / Electronics / General